2021
DOI: 10.1111/cdev.13680
|View full text |Cite
|
Sign up to set email alerts
|

Observed dyadic racial socialization disrupts the association between frequent discriminatory experiences and emotional reactivity among Black adolescents

Abstract: Understanding the underlying mechanisms by which racism degrades mental health and the factors that disrupt these mechanisms is paramount. Black adolescents (Mage = 15.5) and their mothers (Mage = 44) were observed discussing a hypothetical discriminatory situation and surveyed about their discriminatory experiences (N = 110). Results indicated that adolescents’ submissive emotional reactivity (e.g., sadness, embarrassment) in direct response to discrimination, rather than dominant reactivity (e.g., anger, fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 61 publications
(112 reference statements)
1
7
0
Order By: Relevance
“…The current study aligns with a movement in the field toward greater nuance in the measurement of situation‐specific ethnic‐racial socialization between caregivers and children (Dunbar et al, 2022 ). Several limitations are important to note.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The current study aligns with a movement in the field toward greater nuance in the measurement of situation‐specific ethnic‐racial socialization between caregivers and children (Dunbar et al, 2022 ). Several limitations are important to note.…”
Section: Discussionsupporting
confidence: 81%
“…Very little prior research has combined the use of an observational measure of ethnic-racial socialization with a person-centered analytic approach, let alone one that simultaneously captures global aspects of the childcaregiver relationship alongside ethnically and racially socializing constructs. Of the two studies known to these authors (Caughy et al, 2011;Dunbar et al, 2022), neither involved a joint sample of Black and Latinx caregivers, making this study a substantial contribution to the literature on ethnic-racial socialization. In this crosssectional analysis, we observed discussions between caregivers and children as they responded to a hypothetical situation involving a racially and ethnically discriminatory comment made by a school counselor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the reappraisal and decision-making process, they may assess their available coping resources (i.e., disengagement from the issue, venting to others, expressing emotions, or participating in a protest), and start to engage in various behaviors to help resolve their sense of racial stress. In line with this, studies find that Black parents often have conversations with family members, friends, or their children in which they recount personal experiences of racial discrimination (Dunbar et al, 2022;Saleem et al, 2020), communicate fears for their safety (Kincade & Fox, 2022;Mehra et al, 2022), and offer information about coping-related strategies (Leath et al, 2021;Threlfall, 2018). Overall, we use this theory to explore the nature of Black mothers' responses to vicarious racial violence, with a particular focus on racial grief as an understudied, but critical component of the racial stress and coping process.…”
Section: Racial Stress and Coping Among Black Mothersmentioning
confidence: 87%
“…However, most of this work does not distinguish the feeling and constructive expression of anger—a normal and healthy response to acts of injustice—from the behavioral or mental health consequences if emotions go unregulated. Recent work from my colleagues and I found that while Black adolescents who reported experiencing discrimination said they felt anger, frustration, and disrespected, these emotions were not associated with depressive symptoms or the fighting and rule‐breaking behaviors that are typically attributed to an underlying anger problem (Dunbar, HaRim Ahn, Coates, & Smith‐Bynum, 2021 ). Instead, sadness, shame, and embarrassment—which may reflect youths’ internalization of denigrating racist messages and self‐blame—were associated with depression/anxiety and externalizing problems (Dunbar et al., 2021 ).…”
Section: Black Lives and Black Research Mattermentioning
confidence: 99%